Preventive effect of Ibrolipim on suppressing lipid accumulation and increasing lipoprotein lipase in the kidneys of diet-induced diabetic minipigs - Li Hong; Yu Jian; Cai Man; Li Qin; Yin Wei; Wang Zong; Liu Yi; Zhang Chi; Zu Xiu (Lipids in Health and Disease, 2011)
Abstract Background The role of renal lipoprotein lipase (LPL) per se in kidney diseases is still controversial and obscure. The purpose of this study was to observe the preventive effects of Ibrolipim, a LPL activator, on lipid accumulation and LPL expression in the kidneys of minipigs fed a high-sucrose and high-fat diet (HSFD). Methods Male Chinese Bama minipigs were fed a control diet or HSFD with or without 0.1 g/kg/day Ibrolipim for 5 months. Body weight, plasma glucose, insulin, lipids, LPL activity, and urinary microalbumin were measured. Renal tissue was obtained for detecting LPL activity and contents of triglyceride and cholesterol, observing the renal lipid accumulation by Oil Red O staining, and examining the mRNA and protein expression of LPL by real time PCR, Western Blot and immunohistochemistry. Results Feeding HSFD to minipigs caused weight gain, hyperglycemia, hyperinsulinemia, hyperlipidemia and microalbuminuria. HSFD increased plasma LPL activity while it decreased the mRNA and protein expression and activity of LPL in the kidney. The increases in renal triglyceride and cholesterol contents were associated with the decrease in renal LPL activity of HSFD-fed minipigs. In contrast, supplementing Ibrolipim into HSFD lowered body weight, plasma glucose, insulin, triglyceride and urinary albumin concentrations while it increased plasma total cholesterol and HDL-C. Ibrolipim suppressed the renal accumulation of triglyceride and cholesterol, and stimulated the diet-induced down-regulation of LPL expression and activity in the kidney. Conclusions Ibrolipim exerts renoprotective and hypolipidemic effects via the increase in renal LPL activity and expression, and thus the increased expression and activity of renal LPL play a vital role in suppressing renal lipid accumulation and ameliorating proteinuria in diet-induced diabetic minipigs.